Efectos de la zeolita en la fertilización de banano - Contreras Castro, Romel Rolando (2006)
The present investigation that treats on the “Effects of the zeolite in the banana tree fertilization”, I am made in the Property Guarumal de Propiedad of Mr. Miguel Pineda Cobos located in the Guarumal site of the Baloza parish, pertaining to the Corner Santa Rosa, province of Gold. The lenses were the following ones: 1. To determine the best combination of fertilization with zeolitem2. To determine the effects of the application of zeolite in the parición. In the work of investigation 9 combinations studied, these are described next: A1B1 A2B1 A3B A1B2 A2B2 A3B2 A1B3 A2B3 A3B3 The parcels completely distributed within the bananera according to the design of blocks at random in factorial adjustment with 9 combinations and 3 repetitions giving a total of 27 experimental parcels. The analysis of variance of the analyzed variables. The comparison between the averages of the combinations was made by means of the test of Duncan with a significance level of 5%. The mathematical model this represented by the following linear equation with the variance components: Yij = u + r + A +B + (AxB) + Eij The variables in study were:  Height of plant to the parición Thickness of Pseudotallo in plants just paridas  Height of the son or return in harvested plants I number of leaves to the parición On the basis of the obtained results one concluded: The combinations of zeolite with fertilizers increase the absorption of nutrients in the plants. The averages observed for all the variables as much in zeolite as for fertilizers increase in the development of the plant. The averages observed for fertilizers in the different evaluated variables; do not present/display statistical difference. Equal situation appears with the averages obtained in the application of zeolite.